Mental health and therapeutic abortion - Rondón, Marta B. (2015)
The concept of health is reviewed to argue that the mental component as inherent to the integral wellbeing, since mental and physical health are closely related. The relationship between depression and events of the reproductive cycle is described, especially concerning the risk posed by unwanted pregnancy, a risk factor for postpartum depression as reported in studies conducted in various parts of the world. Consequently, women with depression risk factors (history of previous depressive ailment, background of infant adversity or trauma or exposition to violence, family history of affective disorder, poverty and lack of social support, concomitant physical ailments, and altered fetus health) should receive information to allow them to decide if they wish to interrupt pregnancy for therapeutic reasons in order to protect their mental health. Practical recommendations to recognize and manage these women are presented.